Efficacy of Pre-Medication with Ibuprofen on Post-Operative Pain after Pulpotomy in Primary Molars - Shafie, Lili; Esmaili, Sara; Parirokh, Masoud; Pardakhti, Abbas; Nakhaeee, Nouzar; Abbott, Paul V.; Barghi, Hamide (Iranian Endodontic Journal, 2018)
Introduction: Pain management following dental procedures, particularly pulpotomies and extraction, is of great importance in pediatric dentistry. The aim of this study was to investigate the efficacy of pre-treatment with ibuprofen on post-operative pain following pulpotomy of primary molars. Methods and Materials: In a split mouth double-blinded randomized clinical trial, 49 children aging between 6-10 years old were given either ibuprofen or a placebo 45 min prior to the treatment. After pulpotomy and placement of a stainless steel crown (SSC), the pain level was evaluated using the Wong-Baker face visual analogue scale for up to 7 days post-treatment. McNemar and Wilcoxon tests were used for data analysis. Results: Forty-five patients were eligible to participate in this study. Pre-medication with ibuprofen significantly reduced pain during the first 24 h post-treatment (P=0.032). However, there was no significant difference in the pain levels between placebo and ibuprofen groups at 48 and 72 h post-treatment (P=0.154 and P=0.197, respectively). The number of times patients needed analgesics in ibuprofen group was significantly lower compared to that in the placebo group (P=0.008). Conclusion: Pre-medication with ibuprofen resulted in less pain following pulpotomy and SSC placement in primary teeth. Keywords:Ibuprofen; Pre-Medication; Primary Molar; Pulpotomy; Visual Analogue Scale; Wong Baker